Implementasi Metode Cepat Kompresi File Document Otomatis Pada Aplikasi Berbasis Web Menggunakan Algoritma Additive Code - Yuza Reswan; Leo Tri Anggoro (Jurnal Media Infotama, 2024)
Online data entry systems have largely replaced manual file submission in modern data transmission. Data is often very large. Therefore, a method is needed to reduce the size of the data. File compression, or compression in general, is the name of this method. Compressing files involves transforming multiple document files into a standard encoding format to reduce storage space requirements or increase upload speed. The results of this research inform the use of the Additive Code technique application for file compression, which makes it easier to upload document files automatically and is useful for users. Therefore, the author conducted research with the aim of developing a web-based application. This system can make it easier to upload document files so that it can reduce processing time. Using this method in online applications is useful for creating large document files that can be compressed into smaller ones by following the compression procedure. Data compression test results were obtained by running 10 samples of each document and PDF data file at a speed of less than 3 seconds, with accuracy ranging from 27% to 67% for each sample. We successfully tested ten Word documents and ten PDFs that were uploaded and compressed.